Sclerosing angiomatoid nodular transformation of spleen with calcifying fibrous pseudotumor: A rare case with unusual association - Shanthi, Vissa; Rukmangadha, Nandyala; Reddy, Gopinath; Banoth, Manilal (Indian Journal of Case Reports, 2024)
Sclerosing angiomatoid nodular transformation (SANT) of the spleen is a rare benign vascular lesion of the spleen that was first described in 2004. SANT is associated with other concurrent diseases, mostly malignancies. Calcifying fibrous pseudotumor (CFPT) is a tumor-like lesion usually arising from soft tissue or peritoneal sub-serosa. Both SANT and CFPT are considered to be variants of the inflammatory myofibroblastic tumor. We report the rare case of a 24-year-old female presenting with a left abdominal mass that was clinically diagnosed as an extraintestinal gastrointestinal stromal tumor (GIST). Histopathological examination revealed SANT of spleen and CFPT. We report this case due to its rarity of occurrence and unusual association of SANT with CFPT.